From Awareness to Action: How Green Marketing Shapes Purchase Intentions for Sustainable Cosmetics - Jamal, Fauziyah Nur; Yuniarti, Dini; Asih, Hayati Mukti; Jumbri, Isma Addi; Wibowo, Shaneva Fitria Desta (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
Green marketing has intensified as cosmetic companies compete to project environmentally responsible identities, yet converting awareness into actual purchase remains uneven. This study examines the influence of environmental attitude, green brand image, and green perceived value on green purchase intention, drawing on survey data from 150 Body Shop consumers in Indonesia and analyzed with SEM-PLS. Results show that environmental attitude does not significantly predict intention, while both green brand image and green perceived value exert positive effects. These findings indicate that credible brand signals and tangible value perceptions act as more immediate drivers of intention than generalized attitudes, refining how the attitude–behavior gap is understood in sustainable consumption. The study contributes by highlighting the primacy of image and value in shaping intention and provides managerial implications for firms to emphasize credible positioning and consumer value rather than relying solely on environmental appeals to stimulate sustainable purchasing.